Magnetic material, its manufacturing method and iron core
Patent Information
- Application Number
- JP2021074458
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-26
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-04-26
AI Technical Summary
【0012】 本発明によると、材料コストを抑制して高い飽和磁束密度と低い鉄損を両立できる磁性体材料、その製造方法、および、これを用いた鉄心を提供することができる。
Smart Images

Figure 0007645127000002 
Figure 0007645127000003 
Figure 0007645127000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic material in which a cobalt concentration gradient is formed in an iron-cobalt alloy, a manufacturing method thereof, and an iron core.
[0002] Among bulk alloys, the material with the highest saturation magnetic flux density Bs is an iron-cobalt alloy. For example, permendur Fe-49Co-2V has a bulk Bs of 2.3 T, and is widely used in motor cores and other applications as a soft magnetic material with a high Bs. However, iron-cobalt alloys contain cobalt, which is more expensive than iron, and therefore have issues with mass production and cost.
[0003] In recent years, iron nitride α″-Fe has been developed as a magnetic material that is less expensive than iron-cobalt alloys and has a high saturation magnetic flux density Bs equivalent to that of iron-cobalt alloys in the thin film state. 16 N2 is attracting attention. α″-Fe 16 N2 is a body-centered tetragonal (bct) iron-based martensite, and has a crystal structure in which N penetrates α-Fe and the lattice spacing expands in the c-axis direction. α″-Fe 16 The Bs of a thin film of N2 is known to exceed 2.4T.
[0004] Iron nitride α″-Fe 16 N2 is a metastable phase, has low thermal stability, and is known to be difficult to grow. 16 Various research and development efforts are being conducted on N2, including manufacturing methods. Patent Document 1 describes a soft magnetic material including martensite containing carbon and nitrogen, and a manufacturing method thereof. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-132894 A Summary of the Invention [Problem to be solved by the invention]
[0006] In various applications such as rotating electrical machines and transformers, there is a demand for soft magnetic materials that are inexpensive yet have a high saturation magnetic flux density Bs. Conventional iron-cobalt alloys such as permendur contain nearly 50 atomic % Co, so it is desirable to reduce the amount of Co. However, when part of the Co is replaced with another element, the saturation magnetic flux density Bs decreases, the magnetic permeability μ decreases, and the iron loss Pi increases.
[0007] An inexpensive magnetic material that exhibits high saturation magnetic flux density Bs is iron nitride α″-Fe 16 There is also N2, but its poor thermal stability prevents its industrial production. 16 It is expected that the Bs will be further improved by introducing nitrogen atoms into a high Bs iron-cobalt alloy as a substitutional solid solution, such as N2.
[0008] However, nitrogen atoms are difficult to diffuse within the alloy phase of iron-cobalt alloys, and it is not easy to form nitrogen-substituted martensite. It is possible to add Al, Cr, Mo, Nb, V, etc. to iron-cobalt alloys together with nitrogen, but this reduces Fe and Co, lowering the saturation magnetic flux density Bs and the magnetic permeability μ, which increases the iron loss Pi.
[0009] In addition, in applications of soft magnetic materials such as iron cores, not only is it necessary to suppress iron loss Pi, but mechanical properties such as strength and toughness are also required. Mechanical properties must be obtained in a material form that provides appropriate magnetic properties. Regardless of whether or not nitrogen substitution is introduced, there is a demand for soft magnetic materials that are inexpensive and have reduced material costs, yet can achieve high saturation magnetic flux density Bs and low iron loss Pi, and that have a basic composition and structure that allows the introduction of nitrogen substitution and the improvement of mechanical properties.
[0010] Therefore, an object of the present invention is to provide a magnetic material that can achieve both high saturation magnetic flux density and low core loss while suppressing material costs, a manufacturing method thereof, and an iron core using the same. [Means for solving the problem]
[0011] In order to solve the above problems, the magnetic material according to the present invention is a magnetic material containing Fe and Co in a total amount of 90 mass % or more, the magnetic material being in the form of a foil or plate, and containing 5 mass % or more and 40 mass % or less of Co. , and 0.1% to 4.0% by mass of N Including, The ordered phase α″-Fe 16 N 2 and the disordered phase α′-Fe 8 N, In the thickness direction of the foil or plate, there are a high concentration region having a cobalt concentration of 20 mass % or more, a low concentration region having a cobalt concentration of more than 0 mass % and not more than 10 mass %, and a concentration transition region connecting the cobalt concentrations of the high concentration region and the low concentration region. The iron core according to the present invention is an iron core in which soft magnetic steel plates are laminated, and a part or all of the soft magnetic steel plates are formed from the magnetic material. Further, a manufacturing method of a magnetic material according to the present invention is a manufacturing method of a magnetic material containing Fe and Co, the magnetic material being a foil or plate, comprising stacking a precursor formed of an iron-based material having a cobalt concentration of 20 mass% or more and a precursor formed of an iron-based material or a cobalt-based material having a cobalt concentration of more than 0 mass% and not more than 10 mass%, and heat-treating the precursors stacked on top of each other to diffuse atoms, thereby forming a high-concentration region having a cobalt concentration of 20 mass% or more, a low-concentration region having a cobalt concentration of more than 0 mass% and not more than 10 mass%, and a concentration transition region connecting the cobalt concentration of the high-concentration region and the cobalt concentration of the low-concentration region in the thickness direction of the foil or plate. a nitriding heat treatment in which nitrogen is infiltrated and diffused by contacting the precursor or the magnetic material with a nitriding gas under heat treatment; and a cooling step in which the precursor or the magnetic material that has been nitriding heat treated is quenched to transform the precursor or the magnetic material into a martensite structure, thereby obtaining an ordered phase α″-Fe containing 5 mass % or more and 40 mass % or less of Co and 0.1 mass % or more and 4.0 mass % or less of N, and in which the N is dissolved. 16 N 2 and the disordered phase α′-Fe 8 Manufacture of magnetic materials containing at least one of the following: do. Effect of the Invention
[0012] According to the present invention, it is possible to provide a magnetic material that can suppress material costs and simultaneously achieve high saturation magnetic flux density and low core loss, a method for manufacturing the same, and an iron core using the same. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a diagram illustrating an example of a magnetic material according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram illustrating an example of a magnetic material according to an embodiment of the present invention. [Diagram 3] FIG. 1 is a diagram illustrating an example of a magnetic material according to an embodiment of the present invention. [Figure 4] 1A to 1C are diagrams illustrating an example of a method for producing a magnetic material according to an embodiment of the present invention. [Diagram 5] FIG. 1 is a perspective view illustrating an example of a stator of a rotating electric machine. [Figure 6] FIG. 2 is an enlarged schematic cross-sectional view of a slot region of the stator. [Figure 7] 1 is an image showing a backscattered electron image by a scanning electron microscope and the results of composition analysis of a magnetic material according to an embodiment of the present invention. [Figure 8] 1 is an image showing a backscattered electron image by a scanning electron microscope and the results of composition analysis of a magnetic material according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, a magnetic material according to an embodiment of the present invention, a manufacturing method thereof, and an iron core and a rotating electric machine using the same will be described with reference to the drawings. In the following drawings, the same reference numerals are used for common configurations, and duplicated explanations will be omitted.
[0015] <Magnetic material> The magnetic material according to the present embodiment is ferromagnetic at room temperature and is provided in the form of a foil or plate. This magnetic material contains iron (Fe) and cobalt (Co) in a total amount of 90% by mass or more relative to 100% by mass of the material, and contains at least 5% by mass to 40% by mass of Co relative to 100% by mass of the material, and is a magnetic material that exhibits soft magnetism.
[0016] In the magnetic material according to the present embodiment, a concentration gradient of cobalt is formed in the thickness direction perpendicular to the main surface of the foil or plate, in particular. Along the thickness direction of the foil or plate, regions with different cobalt concentrations are formed, and a concentration gradient of cobalt concentration connecting these regions is formed by diffusing cobalt atoms between these regions.
[0017] Specifically, the magnetic material according to the present embodiment has, in the thickness direction of the foil or plate, a high concentration region where the cobalt concentration is relatively high, a low concentration region where the cobalt concentration is relatively low, and a concentration transition region between these regions. The concentration transition region forms a concentration gradient connecting the cobalt concentration of the high concentration region and the cobalt concentration of the low concentration region, and is a region that exhibits a cobalt concentration intermediate between the cobalt concentration of the high concentration region and the cobalt concentration of the low concentration region.
[0018] Conventionally, electric motors such as motors use cores made of laminated foils or sheets of soft magnetic materials, including electromagnetic steel sheets. The thickness of the foils or sheets is about 10 μm to 1 mm. Conventional iron-cobalt alloys such as permendur are soft magnetic materials that exhibit high saturation magnetic flux density Bs, but because they contain expensive cobalt, it is desirable to achieve both low cost and good magnetic properties.
[0019] The magnetic material used in the core is required to exhibit soft magnetism, a saturation magnetic flux density Bs higher than that of pure iron, an iron loss Pi equal to or lower than that of electromagnetic steel sheet, high mechanical strength, good toughness so that it can be processed and laminated, etc. The Bs of pure iron is 2.14 T at 20°C, and it is desirable to be able to achieve a higher Bs at low cost.
[0020] When the amount of Co in an iron-cobalt alloy such as permendur is reduced, the amount of Co, which is expensive compared to Fe, is reduced, and it is possible to obtain a soft magnetic material that is suitable for mass production and is cost-effective. However, when the amount of Co is reduced, the saturation magnetic flux density Bs decreases, and the magnetic permeability μ decreases and the iron loss Pi increases. Increasing the amount of other alloying elements such as Ni can improve the magnetic permeability μ and reduce the iron loss Pi, but this has the problem of lowering Bs and increasing the material cost.
[0021] In addition, iron nitride α″-Fe is an inexpensive magnetic material that exhibits high saturation magnetic flux density Bs. 16 N2 is known. α″-Fe 16 It has been found that N2 can achieve a high Bs of 2.1 to 2.8 T. Iron nitride α″-Fe 16 When nitrogen is added to an iron-cobalt alloy, as in N2, and the nitrogen atoms are made into a substitutional solid solution, there is a possibility that the Bs can be improved, as in the case of iron nitride.
[0022] However, compared to pure iron, nitrogen atoms are less likely to diffuse within the alloy phase of an iron-cobalt alloy, and it is not easy to dissolve nitrogen atoms in a substitutional solid solution. Adding Al, Cr, Mo, Nb, V, etc. together with nitrogen is also an option, but adding many elements reduces the amount of Fe and Co. As the saturation magnetic flux density Bs decreases, the magnetic permeability μ decreases, and the iron loss Pi increases. If nitrogen atoms are dissolved in a substitutional solid solution, the crystal distortion increases, which is also a problem in that Pi increases.
[0023] Under these circumstances, the inventors investigated and examined the interrelationships between various factors such as the form of cobalt concentration distribution, heat treatment time, and magnetic properties of magnetic materials based on iron-cobalt alloys, discovered the effectiveness of a cobalt concentration gradient, and completed the present invention. They discovered that forming a cobalt concentration gradient and providing a high concentration region, a low concentration region, and a concentration transition region provides the advantages of pure iron and permendur, which has high Bs and low Pi, and can achieve both a high saturation magnetic flux density Bs and low iron loss Pi while suppressing material costs.
[0024] 1, 2 and 3 are diagrams each showing a schematic diagram of an example of a magnetic material according to an embodiment of the present invention. 1, 2 and 3, the upper part of each figure shows an example of a layer structure of a magnetic material having a cobalt concentration gradient, and the lower part of each figure shows an outline of the cobalt concentration distribution along the thickness direction of the magnetic material.
[0025] In each figure, reference numerals 1, 2, and 3 indicate magnetic materials forming a cobalt concentration gradient. Reference numeral 100 indicates a high concentration region where the cobalt concentration is relatively high. Reference numeral 200 indicates a low concentration region where the cobalt concentration is relatively low. Reference numeral 300 indicates a concentration transition region between the high concentration region and the low concentration region.
[0026] As shown in Fig. 1, the magnetic material according to this embodiment can be provided in a two-layer structure in which, for example, a high concentration region 100 / (concentration transition region 300) / low concentration region 200 are laminated in this order. The high concentration region 100 and the low concentration region 200 have different magnetic properties. However, in applications in which foil or plate magnetic materials are laminated, even with such a two-layer structure, the geometric magnetic anisotropy can be reduced.
[0027] As shown in Fig. 2, the magnetic material according to this embodiment can be provided in a three-layer structure in which a low concentration region 200 / (concentration transition region 300) / high concentration region 100 / (concentration transition region 300) / low concentration region 200 are laminated in this order. Also, as shown in Fig. 3, the magnetic material can be provided in a three-layer structure in which a high concentration region 100 / (concentration transition region 300) / low concentration region 200 / (concentration transition region 300) / high concentration region 100 are laminated in this order.
[0028] The high concentration region 100, the low concentration region 200, and the concentration transition region 300 are not particularly limited in thickness or volume ratio per magnetic material. The thickness of each region can be set to any thickness depending on the required performance, material cost, etc. From the viewpoint of manufacturability, the thickness of the high concentration region 100 and the low concentration region 200 is preferably about 0.1 μm or more and 0.5 mm or less.
[0029] Furthermore, the cobalt concentration in each of the high concentration region 100, the low concentration region 200, and the concentration transition region 300 is not particularly limited. The cobalt concentration in the high concentration region 100 and the low concentration region 200 can be set to any concentration within a predetermined range depending on the required performance, material costs, etc. The cobalt concentration in the high concentration region 100 and the low concentration region 200 may be substantially uniform along the thickness direction in each region, or may form a concentration gradient.
[0030] 1, 2, and 3, the concentration transition region 300 is illustrated as an independent layer, but the concentration transition region 300 does not have to have a clear boundary with the high concentration region 100 or the low concentration region 200. As long as the concentration transition region 300 shows a cobalt concentration intermediate between the high concentration region 100 and the low concentration region 200 in elemental analysis, it does not have to show a linearly changing concentration distribution, and may show a curved or stepwise changing concentration distribution.
[0031] 1, 2 and 3 show a two-layer structure or a three-layer structure, the high concentration regions 100 and the low concentration regions 200 may be provided in a layer structure of four or more layers as long as a concentration transition region 300 is interposed between the regions. Either the high concentration region 100 or the low concentration region 200 may be located on both main surfaces of the foil or plate of the magnetic material.
[0032] The high concentration region (100) is a region having a cobalt concentration of 20 mass% or more relative to 100 mass% of the magnetic material. By forming a high concentration region with a relatively high cobalt concentration, the saturation magnetic flux density Bs of the magnetic material can be improved compared to that of pure iron. In addition, since a high magnetic permeability μ can be obtained, the iron loss Pi of the magnetic material can be reduced.
[0033] The high-concentration region may be configured to have a Co content of 20 mass% or more, and may optionally contain one or more of nitrogen (N), carbon (C), nickel (Ni), manganese (Mn), silicon (Si), chromium (Cr), titanium (Ti), niobium (Nb), and vanadium (V), with the balance being iron (Fe) and unavoidable impurities. A preferred form of the high-concentration region is a composition that does not contain any of these elements, a composition that contains only N among these elements, or a composition that contains N and C.
[0034] The amount of Co in the high concentration region may be 25% by mass or more, 30% by mass or more, 35% by mass or more, 40% by mass or more, etc. With a large amount of Co, a high saturation magnetic flux density Bs is obtained. In addition, a high magnetic permeability μ is obtained, so that the iron loss Pi is reduced. The amount of Co in the high concentration region is preferably 40% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less, and even more preferably 25% by mass or less. The smaller the amount of Co, the cheaper the magnetic material is obtained.
[0035] The low-concentration region (200) is a region having a cobalt concentration of more than 0 mass% and not more than 10 mass% relative to 100 mass% of the magnetic material. By forming a low-concentration region with a relatively low cobalt concentration, the magnetic material contains less cobalt, making it possible to obtain a magnetic material that is inexpensive and suitable for industrial production.
[0036] The low-concentration region may be configured such that Co is more than 0 mass% and not more than 10 mass%, and may optionally contain one or more of nitrogen (N), carbon (C), nickel (Ni), manganese (Mn), silicon (Si), chromium (Cr), titanium (Ti), niobium (Nb), and vanadium (V), with the balance being iron (Fe) and unavoidable impurities. A preferred form of the low-concentration region is a composition that does not contain any of these elements, a composition that contains only N among these elements, or a composition that contains N and C.
[0037] The amount of Co in the low concentration region may be 8 mass% or less, 6 mass% or less, 4 mass% or less, 2 mass% or less, etc. The smaller the amount of Co, the cheaper the magnetic material is obtained. The amount of Co in the low concentration region may be 1 mass% or more, 3 mass% or more, 5 mass% or more, 7 mass% or more, etc. The larger the amount of Co, the higher the saturation magnetic flux density Bs is obtained. In addition, since a high magnetic permeability μ is obtained, the iron loss Pi is reduced.
[0038] The concentration transition region (300) is a region that connects the cobalt concentration of the high concentration region and the cobalt concentration of the low concentration region. In other words, it is a region that has a cobalt concentration intermediate between the cobalt concentration of the high concentration region and the cobalt concentration of the low concentration region. The concentration transition region is formed by diffusing cobalt atoms between the precursor of the high concentration region and the precursor of the low concentration region, which have different cobalt concentrations. When the concentration transition region is formed, the magnetization state such as a domain wall is easily propagated between the high concentration region and the low concentration region.
[0039] The concentration transition region has an intermediate chemical composition between the high concentration region and the low concentration region. The concentration transition region contains an amount of Co according to the chemical composition of the high concentration region and the low concentration region, and like the high concentration region and the low concentration region, optionally contains one or more of nitrogen (N), carbon (C), nickel (Ni), manganese (Mn), silicon (Si), chromium (Cr), titanium (Ti), niobium (Nb) and vanadium (V), with the remainder being iron (Fe) and unavoidable impurities.
[0040] According to the magnetic material with such a cobalt concentration gradient, a high concentration region, a low concentration region, and a concentration transition region are formed, and the advantages of both pure iron and permendur are obtained, so that it is possible to suppress material costs and achieve both high saturation magnetic flux density Bs and low iron loss Pi. Since a high magnetic permeability μ is secured, it is useful as a soft magnetic material. In addition, since a low concentration region where the cobalt concentration is relatively low is formed, nitrogen atoms can easily diffuse in the low concentration region. Therefore, when nitrogen atoms are made into a substitutional solid solution, Bs can be appropriately improved even if the additive element that has an affinity with nitrogen is reduced or omitted.
[0041] The concentration gradient of the cobalt concentration in the concentration transition region is preferably 0.1 mass% / μm or more and 10 mass% / μm or less. If the concentration gradient is less than 0.1 mass% / μm, the difference in cobalt concentration between the high concentration region and the low concentration region is small, making it difficult to sufficiently suppress material costs. On the other hand, if the concentration gradient exceeds 10 mass% / μm, the concentration gradient is too steep, making it difficult to generate magnetic coupling between the high concentration region and the low concentration region.
[0042] Here, the chemical composition of the entire material in the magnetic material in which a cobalt concentration gradient is formed will be specifically described. In the following description, "%" means mass %.
[0043] (Fe, Co: 90% or more) Fe and Co are the main components of the magnetic material according to this embodiment, and contribute to improving the magnetic properties. If the total amount of Fe and Co is less than 90%, magnetic properties such as high saturation magnetic flux density Bs, high magnetic permeability μ, and small coercive force Hc cannot be obtained. On the other hand, if it is 90% or more, good magnetic properties required for soft magnetic materials can be obtained. Therefore, the total amount of Fe and Co is set to 90% or more in the entire magnetic material.
[0044] (Co:5% or more and 40% or less) Co is a main component of the magnetic material according to this embodiment, and forms a concentration gradient, contributing to the improvement of magnetic properties. If the amount of Co is less than 5%, the effect of adding Co cannot be obtained. If the amount of Co is 5% or more, a high saturation magnetic flux density Bs can be obtained. In addition, since a high magnetic permeability μ can be obtained, the iron loss Pi can be reduced. On the other hand, if the amount of Co exceeds 40%, the chemical composition becomes close to that of conventional permendur, and the material cost becomes high. If the amount of Co is 40% or less, the material cost can be reduced more than before. Therefore, the amount of Co is 5% or more and 40% or less in the entire magnetic material. The amount of Co is preferably 10% or more. In addition, the amount of Co is preferably 35% or less.
[0045] (N: 0% or more and 4.0% or less) N contributes to improving the mechanical and magnetic properties, especially the saturation magnetic flux density Bs. The iron nitride phase is the ordered α″-Fe 16 There are two types of N: N2 or disordered phase α'-Fe8N and γ'-Fe4N. The former has a high Bs, while the latter has a low Bs. When the former is formed, a magnetic material with a high Bs is obtained. If the N content exceeds 4.0%, it becomes easy for low magnetic γ'-Fe4N to form, and good magnetic properties cannot be obtained. If the N content is 4.0 or less, α″-Fe 16 N2 can provide good magnetic properties and mechanical properties. Therefore, the N content is set to 0% or more and 4.0% or less in the entire magnetic material. The N content is preferably 0.1% or more. Also, the N content is preferably 1.0% or less.
[0046] (C: 0% or more and 1.0% or less) C contributes to improving mechanical and magnetic properties. When combined with N, C forms Fe-CN iron nitrides, and acts to improve Bs in the same way as N. If the C content exceeds 1.0%, low-magnetic carbides and the like are easily generated, and good magnetic properties cannot be obtained. If the C content is 1.0 or less, good magnetic properties can be obtained due to iron nitrides in which C is dissolved. Therefore, the C content is set to 0% or more and 1.0% or less in the entire magnetic material. The C content is preferably 0.5% or less.
[0047] (Ni: 0% or more and 2.0% or less) Ni contributes to improving corrosion resistance, mechanical properties, temperature properties, etc. Ni exhibits relatively high magnetic permeability μ and magnetic moment, but its magnetic properties are inferior to Fe and Co. In addition, Ni is relatively expensive, and when N is made into a substitutional solid solution, it reduces the amount of N in solid solution. Therefore, the Ni content is set to 0% or more and 2.0% or less in the entire magnetic material.
[0048] (Mn, Si, Cr, Ti, Nb, V: 0% or more and 0.2% or less) Mn, Si, Cr, Ti, Nb, and V contribute to improving mechanical properties. These elements form precipitates to improve strength and toughness and reduce iron loss Pi. However, adding large amounts of these elements reduces the amounts of Fe and Co, which are major components. In addition, when combined with N and C, they form low-magnetic nitrides and carbides. Therefore, the amount of these elements should be between 0% and 0.2% in the entire magnetic material.
[0049] (Inevitable impurities) Examples of the unavoidable impurities include hydrogen (H), phosphorus (P), sulfur (S), oxygen (O), magnesium (Mg), calcium (Ca), copper (Cu), zinc (Zn), tin (Sn), etc. The unavoidable impurities are preferably 0.01% by mass or less, and more preferably 0.001% by mass or less, for each element.
[0050] The chemical composition of magnetic materials can be confirmed by a scanning electron microscope (SEM)-energy dispersive X-ray spectroscopy (EDX), an electron probe micro analyzer (EPMA), etc. The crystal structure of magnetic materials can be confirmed by X-ray diffraction (XRD) measurement.
[0051] <Method of manufacturing magnetic materials> The magnetic material according to this embodiment can be manufactured by stacking a precursor of a high concentration region and a precursor of a low concentration region, and diffusing cobalt atoms between the precursors. A foil or a plate can be used as the precursor for each region. A thin film formed on the surface of a foil or a plate can also be used as the precursor.
[0052] FIG. 4 is a diagram showing an example of a method for manufacturing a magnetic material according to an embodiment of the present invention. As shown in FIG. 4, the magnetic material having a cobalt concentration gradient can be produced by a production method including a raw material mixing and melting step S1, a casting step S2, an annealing step S3, a first rolling step S4, a first annealing step S5, a second rolling step S6, a second annealing step S7, a lamination step S8, and a diffusion layer forming step S9.
[0053] 1, the raw material mixing and melting step S1 includes a raw material alloy ingot forming step S1a and a remelting step S1b. The lamination step S8 can be selected from a cladding process step S8a or a physicochemical lamination step S8b.
[0054] The steps from the raw material mixing and melting step S1 to the secondary annealing step S7 can be carried out to produce a foil or plate precursor. These steps can produce a high-concentration region precursor, a low-concentration region precursor, or both. However, these steps are merely examples, and not all of these steps are essential. Some steps can be omitted, or multiple steps can be combined into a continuous process.
[0055] (Raw material mixing and dissolving process) The raw material mixing and melting step S1 is a step of mixing and melting the raw materials of the magnetic material. The raw materials of the magnetic material, such as metals, are charged into a melting furnace so as to have a desired chemical composition, and are heated and mixed to form a molten metal 30. The method of melting the raw materials is not particularly limited. As the melting furnace for melting the raw materials, an appropriate furnace such as an induction furnace, an arc type electric furnace, or a resistance furnace can be used.
[0056] As the raw material, when preparing a precursor of a high concentration region, it is possible to use an iron-based material such as alloy steel, iron-cobalt alloy, etc., which is low carbon and low alloy element and has Co: 20 mass % or more, or a cobalt-based material such as pure cobalt. Also, when preparing a precursor of a low concentration region, it is possible to use pure iron, which is Co: 10 mass % or less, or an iron-based material such as steel, alloy steel, electromagnetic steel, iron-cobalt alloy, etc., which is low carbon and low alloy element. When melting, refining such as melt refining or extra-furnace refining may be performed depending on the chemical composition.
[0057] The raw material mixing and melting step S1 preferably includes a raw material alloy ingot forming step S1a and a re-melting step S1b. The raw material alloy ingot forming step S1a is a step of mixing and melting raw materials of the magnetic material, and solidifying the molten metal 10 to produce the alloy ingot 11. The re-melting step S1b is a step of re-melting the alloy ingot 31.
[0058] By carrying out the raw alloy ingot formation step S1a and the remelting step S1b, the alloy ingot 11 that was once melted is remelted, so that it is possible to remove inclusions that float up during remelting and to reduce macrosegregation that occurs during solidification. As a result, it is possible to obtain a purified molten metal 32 with high cleanliness, in which inevitable impurities such as O, P, and S and macrosegregation are reduced.
[0059] There is no particular limitation on the method for remelting the alloy ingot 31. From the viewpoints of reducing costs and obtaining the required refining effect, it is preferable to remelt the alloy ingot 31 by a vacuum arc remelting (VAR) method or an electro slag remelting (ESR) method.
[0060] (Casting process) The casting step S2 is a step in which the molten metal obtained by melting the raw materials is solidified to cast the material for rolling processing. The molten metal 30 is poured into a mold to form a slab-shaped cast body 50. When the remelting step S1b is performed, the purified molten metal 32 is poured into the mold to form a highly clean cast body 50.
[0061] The thickness of the cast body 50 and the casting method are not particularly limited. The thickness of the cast body 50 can be, for example, 1 to 3 mm. Casting can be performed by an appropriate method such as continuous casting, precision casting, sand casting, metal mold casting, etc. Continuous casting can be performed integrally and continuously with the subsequent steps. Precision casting may be a casting method that does not use wax, so long as it forms a plate- or foil-shaped cast body 50 that is close to the shape of the final product.
[0062] In precision casting and other casting, a large alloy ingot may be cast once, the resulting alloy ingot may be divided into pieces of appropriate size, and the divided alloy pieces may be remelted and then cast. When using such a casting method, it is preferable to make the solidification rate faster than that of a general steel plate, etc., from the viewpoint of suppressing the coarsening of crystal grains. The cooling method for the cast may be contact conduction cooling, water cooling, forced air cooling, etc.
[0063] (Annealing process) The annealing step S3 is a step of fully annealing the cast compact. The cast compact 50 is heat-treated at a temperature higher than the eutectoid temperature (A1 transformation point) of the iron-cobalt system to homogenize the cast structure. The heat treatment temperature is preferably 1000°C or higher.
[0064] (First rolling process) The first rolling step S4 is a step of first rolling the cast compact. In the first rolling, the cast compact 50 is rolled to a predetermined intermediate rolling ratio (rolling reduction). The first rolling can be cold rolling. For example, a compact having a thickness of 1 to 3 mm can be cold rolled to 0.2 mm. The rolling load in the first rolling can be, for example, 1 to 10 kN.
[0065] (First annealing process) The first annealing step S5 is a step of intermediate annealing the first rolled material. The first rolled material 60 is heat treated to perform stress relief annealing, and the residual stress remaining after the first rolling is relaxed. By removing the processing stress, the magnetic properties of the magnetic material, particularly the iron loss Pi, can be reduced. The heat treatment temperature is preferably 1000°C or higher.
[0066] (Secondary rolling process) The secondary rolling step S6 is a step of secondary rolling the primary rolled material. In the secondary rolling, the primary rolled material 60 is rolled to a thickness required for the precursor of the high concentration region or the precursor of the low concentration region. For example, the primary rolled material 60 of 0.2 mm can be cold rolled to 0.1 mm. The rolling load of the secondary rolling can be, for example, 4 to 6 kN.
[0067] (Secondary annealing process) The secondary annealing step S7 is a step of intermediate annealing the secondary rolled material. The secondary rolled material is heat treated to perform stress relief annealing, and the residual stress remaining after the secondary rolling is relaxed. Removing the processing stress can reduce the magnetic properties of the magnetic material, particularly the iron loss Pi. The heat treatment temperature is preferably 1000°C or higher.
[0068] (Lamination process) The lamination step S8 is a step of laminating the precursor of the high concentration region and the precursor of the low concentration region. In the lamination step S8, a rolled material rolled to a predetermined thickness can be used as the precursor of the high concentration region or the precursor of the low concentration region. In the lamination step S8, a cladding process step S8a or a chemical lamination step S8b is performed depending on the method of laminating the precursors.
[0069] The cladding process S8a is a process of joining the precursor of the high concentration region and the precursor of the low concentration region by mechanical processing. Depending on the layer structure of the magnetic material to be manufactured, the precursor of the high concentration region and the precursor of the low concentration region are overlapped and pressed or welded together. When the layer structure includes multiple regions of at least one of the high concentration region and the low concentration region, the precursor of the high concentration region and the precursor of the low concentration region are alternately laminated.
[0070] In the cladding process S8a, the precursor of the high concentration region can be a foil or plate made of an iron-based material containing 20% or more by mass of Co or a cobalt-based material such as pure cobalt.The precursor of the low concentration region can be a foil or plate made of an iron-based material containing more than 0% by mass of Co and 10% or less by mass of Co.
[0071] The precursors can be bonded to each other by any suitable method such as hot welding (rolling), cold welding (rolling), friction welding, ultrasonic bonding, etc. The precursors can be bonded to each other by any suitable device such as a rolling roll, a press, a friction welding machine, an ultrasonic metal bonding machine, etc.
[0072] The bonding of the precursors does not need to involve diffusion of cobalt atoms as long as the precursors can be temporarily fixed to each other. If the precursors are fixed to each other without being bonded by compression or welding, it is possible to omit the cladding process S8a.
[0073] The physicochemical lamination step S8b is a step of laminating the precursor of the high concentration region and the precursor of the low concentration region by a physical film formation method or a chemical film formation method. Depending on the layer structure of the magnetic material to be manufactured, a thin film is formed on one or both sides of either the precursor of the high concentration region or the precursor of the low concentration region as the precursor of the other.
[0074] In the physicochemical lamination step S8b, a foil or plate made of an iron-based material containing 20% or more by mass of Co can be used as the precursor of the high concentration region, or a thin film made of an iron-based material containing 20% or more by mass of Co or a thin film made of a cobalt-based material such as pure cobalt can be formed. A foil or plate made of an iron-based material containing more than 0% by mass of Co and not more than 10% by mass of Co can be used as the precursor of the low concentration region, or a thin film made of an iron-based material containing more than 0% by mass of Co and not more than 10% by mass of Co can be formed.
[0075] The film formation method may be a physical film formation method such as vacuum deposition, sputtering, or ion plating, or a chemical film formation method such as electroplating or electrolytic plating. When a chemical film formation method is used, it is preferable to use a foil or plate as the precursor of the low concentration region and to form a thin film as the precursor of the high concentration region. It is also preferable to form a pure cobalt film as the precursor of the high concentration region.
[0076] In the lamination step S8, either the cladding step S8a or the chemical lamination step S8b may be performed depending on the layer structure of the magnetic material to be manufactured, or both may be performed in combination. As the precursor of the high concentration region and the precursor of the low concentration region, a foil or plate of an appropriate thickness may be used, or a thin film of an appropriate thickness may be formed, depending on the target thickness of each region constituting the magnetic material.
[0077] The diffusion layer forming step S9 is a step of diffusing atoms by heat treating the precursor of the high concentration region and the precursor of the low concentration region. The precursor of the high concentration region and the precursor of the low concentration region stacked on top of each other are heat treated to diffuse cobalt atoms and the like between the precursors. When the material is cooled after the diffusion of the cobalt atoms, a concentration transition region is formed near the interface between the precursor of the high concentration region and the precursor of the low concentration region, and a magnetic material having a cobalt concentration gradient is obtained.
[0078] The temperature of the heat treatment for diffusing atoms is preferably 800°C or more and 1200°C or less. At 800°C or more, the diffusion speed of atoms is sufficiently high, so that the concentration gradient of cobalt can be formed in a short time. Also, at 1200°C or less, impurities are less likely to be mixed in, the precursor does not melt, and coarsening of crystal grains can be suppressed. The time of the heat treatment is preferably 0.1 hours or more and 12 hours or less. The heat treatment for diffusing atoms is preferably performed under an inert gas atmosphere such as argon gas.
[0079] In the diffusion layer formation step S9, atoms are diffused by heat treatment, so that a concentration transition region is formed near the interface between the precursor of the high concentration region and the precursor of the low concentration region. This makes it easier for the magnetization state to propagate between the regions. In addition, since cobalt atoms and the like are diffused, the mechanical properties of the magnetic material can be improved. In addition, since processing strain caused by cladding processing and the like can be removed, the magnetic properties of the magnetic material, particularly the iron loss Pi, can be reduced.
[0080] In the above steps, the cast compact is subjected to multiple cold rolling and intermediate annealing, but the method for producing the precursor of the high concentration region and the precursor of the low concentration region is not limited to these methods. The precursor of the high concentration region and the precursor of the low concentration region may be produced by hot rolling or a combination of hot rolling and cold rolling. In addition, the raw material mixing and dissolving step S1 and the subsequent steps may be performed continuously and integrally by roll casting to form multiple layers.
[0081] <Elemental substitution in magnetic materials> The magnetic material according to the present embodiment may have a chemical composition in which N is more than 0 mass% and not more than 4.0 mass% in the entire material, and nitrogen atoms may be substitutionally dissolved. That is, the magnetic material according to the present embodiment contains nitrogen (N) in an amount of more than 0 mass% and not more than 4.0 mass%, and is an ordered phase α″-Fe 16 The magnetic material may contain at least one of N2 and disordered phase α'-Fe8N.
[0082] Regular phase α″-Fe 16 N2 has a crystal structure in which N penetrates α-Fe and the lattice spacing expands in the c-axis direction, is a body-centered tetragonal (bct) system, and exhibits a high saturation magnetic flux density Bs. 16 Although it is not always possible to clearly distinguish between N2 and the disordered phase α′-Fe8N, the inclusion of these iron nitride phases tends to result in a high Bs.
[0083] The magnetic material according to the present embodiment contains more than 0 mass % and not more than 4.0 mass % nitrogen (N), and has an ordered phase α″-Fe 16 The magnetic material may be one in which part or all of the iron (Fe) contained in at least one of N2 and the disordered phase α'-Fe8N is replaced with cobalt (Co).
[0084] Regular phase α″-Fe 16 The N2 or disordered phase α'-Fe8N may be present in any of the high concentration region, low concentration region, and concentration transition region, but is preferably present at least in the low concentration region. These iron nitride phases are stably formed in the low concentration region due to atomic diffusivity, and therefore can improve the magnetic properties of the magnetic material in which a cobalt concentration gradient is formed.
[0085] As a method for synthesizing the iron nitride phase, a method can be used in which a precursor of a high concentration region or a precursor of a low concentration region is used as the treated material and a nitrous heat treatment is performed before the diffusion layer formation step S9. Also, a method can be used in which a magnetic material having a cobalt concentration gradient is used as the treated material and a nitrous heat treatment is performed after the diffusion layer formation step S9.
[0086] Specifically, when synthesizing an iron nitride phase, a precursor of a high concentration region, a precursor of a low concentration region, or a magnetic material in which a concentration gradient of cobalt is formed can be subjected to a nitrous heat treatment process and a cooling process. The thickness of the material to be treated is preferably, for example, 0.01 mm or more and 1 mm or less. In view of the diffusibility of atoms, it is preferable to treat at least the precursor of the low concentration region out of the precursor of the high concentration region and the precursor of the low concentration region.
[0087] When a precursor of a high concentration region or a precursor of a low concentration region is used as the material to be treated, it is preferable to subject the material to a homogenization heat treatment process in advance. The homogenization heat treatment process is a process in which the material to be treated is heated to the austenite formation temperature (Ac3 transformation point) or higher to homogenize it. The homogenization heat treatment is performed under an inert gas atmosphere such as argon gas. For example, the material to be treated is heated to 900°C or higher to diffuse the chemical components in the material into a highly uniform state.
[0088] The nitrous heat treatment process is a process in which a nitrous gas is brought into contact with the material being heat treated, and nitrogen penetrates and diffuses into the material being treated. The nitrous heat treatment is preferably carried out at a temperature higher than the eutectoid temperature (A1 transformation point). This is because nitrogen is easily dissolved in the γ phase and the like. For example, the gas-cooled material is heated to 700 to 900°C and 1×10 5 Nitrogen immersion gas adjusted to about Pa is supplied. As the nitrogen immersion gas, ammonia or the like can be used.
[0089] The nitrous heat treatment step can also be carried out during the diffusion layer formation step S9. If a nitrous gas is supplied while cobalt atoms or the like are being diffused in an inert gas atmosphere, nitrogen can penetrate and diffuse into the matrix of the magnetic material, forming a substitutional solid solution.
[0090] The cooling process is a process in which the material to be treated is quenched to a martensite transformation temperature (Ms transformation point) or lower to cause a phase transformation to a body-centered tetragonal (bct) martensite structure. The quenching can be a process in which the material is cooled to less than 100°C using a coolant such as oil or water, or preferably a sub-zero process in which the material is cooled to 0°C or lower using a coolant such as dry ice or liquid nitrogen.
[0091] When the treated material is quenched after nitrogen immersion heat treatment, nitrogen atoms are dissolved in the matrix, and the ordered phase α″-Fe 16 The result is a magnetic material in which N2 or the disordered phase α'-Fe8N is formed. Nitrogen atoms diffuse more easily into the Fe phase than into the alloy phase, so that the iron nitride phase can be formed at a high volume fraction, especially in the low concentration region.
[0092] The magnetic material according to the present embodiment contains more than 0 mass % and not more than 4.0 mass % nitrogen (N) and more than 0 mass % and not more than 1.0 mass % carbon (C), and is an ordered phase α″-Fe 16 The magnetic material may be one in which a portion of the nitrogen (N) contained in at least one of N2 and the disordered phase α'-Fe8N is replaced with carbon (C).
[0093] When replacing a part of the nitrogen with carbon, the material is subjected to a carburizing treatment at a temperature higher than the eutectoid temperature (A1 transformation point) before the cooling step and before or after the nitriding heat treatment step. The carburizing treatment can be performed, for example, by gas carburizing. The carburizing gas can be acetylene, methane, propane, butane, etc. The carburizing gas can be supplied continuously or intermittently under an inert gas atmosphere.
[0094] When replacing a portion of the nitrogen with carbon, it is preferable to form carbides by subjecting the material to carburizing treatment at a temperature higher than the eutectoid temperature (A1 transformation point) and then cooling to around 200° C. Then, after forming the carbides, it is preferable to heat the material to around the eutectoid temperature (A1 transformation point) and hold it there, then rapidly heat it to or above the austenite formation temperature (Ac3 transformation point) and rapidly cool it.
[0095] For example, the material to be treated, which has been cooled after carburization to generate carbides, is heated to and held at 700 to 900°C, and then rapidly heated to 900°C or higher. The heating rate of the rapid heating is preferably 100°C / sec or higher. The rapid heating is preferably a process in which the material is held at around 950°C for about 1 second.
[0096] In this way, when the material is heated to near the eutectoid temperature, the carbides can be dispersed in a phase with a lower carbon solubility limit than the gamma phase. When the material is then rapidly heated, the carbides dispersed in the matrix are rapidly decomposed, allowing the carbon atoms to be uniformly dissolved. Therefore, when the material is rapidly cooled, a material is obtained in which part of the nitrogen has been uniformly replaced with carbon.
[0097] <Soft magnetic steel plate> The magnetic material according to the present embodiment can be used in the form of a foil or plate-shaped soft magnetic steel sheet. The soft magnetic steel sheet is a steel sheet exhibiting soft magnetism formed from the magnetic material, and has a cobalt concentration gradient formed therein, including a high concentration region, a low concentration region, and a concentration transition region. The thickness of the soft magnetic steel sheet is, for example, 1 μm or more and 1 mm or less.
[0098] The soft magnetic steel sheet may be in the form of a laminate of foil or plate magnetic materials having a cobalt concentration gradient, a high concentration region, a low concentration region, and a concentration transition region. As long as the laminated soft magnetic steel sheet includes such magnetic materials, it may include low carbon steel sheets, electromagnetic pure iron sheets, electromagnetic steel sheets, iron-silicon alloy sheets, iron-cobalt alloy sheets, etc.
[0099] <Iron cores / rotating electric machines> The soft magnetic steel plate using the magnetic material according to the present embodiment can be used as a material for an iron core. The iron core is formed by punching and laminating soft magnetic steel plates. Such an iron core can be used in the stator of a rotating electric machine. The iron core may include a low carbon steel plate, an electromagnetic pure iron plate, an electromagnetic steel plate, an iron-silicon alloy plate, an iron-cobalt alloy plate, etc., as long as the iron core uses a foil or plate magnetic material having a cobalt concentration gradient and a high concentration region, a low concentration region, and a concentration transition region.
[0100] Fig. 5 is a perspective view showing a typical example of a stator of a rotating electric machine. Fig. 6 is a cross-sectional view showing an enlarged schematic view of a slot region of the stator. Note that the cross-sectional view means a cross section perpendicular to the direction of the rotation axis (a cross section whose normal line is parallel to the direction of the rotation axis). In the rotating electric machine, a rotor (not shown) is disposed radially inside the stator shown in Figs. 5 and 6.
[0101] As shown in Figures 5 and 6, stator 10 has stator coils 20 wound in a plurality of stator slots 12 formed on the inner periphery of iron core 11. Stator slots 12 are spaces that are arranged and formed at a predetermined circumferential pitch around the circumferential direction of iron core 11 and penetrate in the axial direction, with slits 13 opening and formed in the innermost periphery and extending in the axial direction. The areas separating adjacent stator slots 12 are referred to as teeth 14 of iron core 11. The portions of inner periphery tip areas of teeth 14 that define slits 13 are referred to as tooth claw portions 15.
[0102] The stator coil 20 is usually composed of a plurality of segment conductors 21. For example, in Fig. 5 to Fig. 6, the stator coil 20 is composed of three segment conductors 21 corresponding to the U-phase, V-phase, and W-phase of a three-phase AC. In order to prevent partial discharge between the segment conductors 21 and the iron core 11 and partial discharge between the phases (U-phase, V-phase, W-phase), the outer periphery of each segment conductor 21 is usually covered with an electrical insulating material 22 (e.g., insulating paper or enamel coating).
[0103] The iron core and rotating electric machine using the soft magnetic steel sheet according to this embodiment are an iron core 11 formed by laminating multiple soft magnetic steel sheets according to this embodiment in a predetermined shape in the axial direction, and a rotating electric machine using the iron core 11. Since soft magnetic steel sheets exhibit magnetic properties of a saturation magnetic flux density Bs exceeding that of pure iron and a coercive force Hc equal to or less than that of pure iron, it is possible to provide an iron core with higher conversion efficiency between electric energy and magnetic energy than an iron core using a conventional electromagnetic steel sheet. A highly efficient iron core can realize a smaller rotating electric machine and higher torque.
[0104] In addition, the soft magnetic steel plate according to this embodiment can be made of low-carbon steel plate, electromagnetic pure iron plate, etc., which have lower material costs than Fe-Co steel plate, and therefore has the advantage of being able to provide highly efficient iron cores and rotating electric machines at low cost.
[0105] A rotating electric machine using the soft magnetic steel plate according to this embodiment in its iron core includes such a stator (core) 10, a stator coil 20, and a rotor. In the stator (core) 10, the teeth 14, tooth claw portions 15, and back yoke of the iron core 11 have a cobalt concentration gradient formed therein, and contain a foil or plate magnetic material having a high concentration region, a low concentration region, and a concentration transition region, so that a high saturation magnetic flux density Bs can be obtained while keeping material costs down.
[0106] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible within the scope of the present invention. For example, the present invention is not necessarily limited to having all the configurations of the above embodiment. It is possible to replace a part of the configuration of an embodiment with another configuration, add a part of the configuration of an embodiment to another form, or omit a part of the configuration of an embodiment. EXAMPLES
[0107] The present invention will be specifically described below with reference to examples, but the technical scope of the present invention is not limited to these examples.
[0108] (Example T-1) A magnetic material with a cobalt concentration gradient was created, and the saturation magnetic flux density Bs, iron loss Pi, metal structure, and chemical composition were evaluated. An Fe-50Co alloy foil material was used as the precursor for the high concentration region. A pure Fe foil material was used as the precursor for the low concentration region, and was half the thickness of the precursor for the high concentration region. The magnetic material had a three-layer structure, with the low concentration region / (concentration transition region) / high concentration region / (concentration transition region) / low concentration region stacked in that order.
[0109] The precursor of the high concentration region was used as the core material, and the precursor of the low concentration region was used as the skin material, and both sides of the core material were clad with the skin material to obtain a laminate having the chemical composition shown in Table 1. This laminate was heat-treated under the conditions shown in Table 1 to obtain a magnetic material according to Example T-1 having a three-layer structure with a cobalt concentration gradient. The thickness was about 200 μm. The obtained magnetic material was subjected to measurement of saturation magnetic flux density Bs, measurement of iron loss Pi, observation of metal structure, and composition analysis.
[0110] (Example T-2) A magnetic material according to Example T-2 having a three-layer structure with a cobalt concentration gradient was prepared in the same manner as in Example T-1, except that the heat treatment conditions were changed as shown in Table 1. The magnetic material was subjected to measurement of saturation magnetic flux density Bs, measurement of iron loss Pi, observation of metal structure, and composition analysis.
[0111] (Comparative example C-1) The foil material according to Comparative Example C-1, which has the chemical composition shown in Table 1 and is a bulk (single-layer structure) having no concentration gradient of cobalt, was subjected to measurement of saturation magnetic flux density Bs and iron loss Pi. The thickness was about 200 μm.
[0112] (Comparative example C-2) The foil material according to Comparative Example C-2, which has the chemical composition shown in Table 1 and is a bulk material having no concentration gradient of cobalt (single-layer structure), was subjected to measurement of saturation magnetic flux density Bs and iron loss Pi. The thickness was about 200 μm.
[0113] (Comparative example C-3) The foil material according to Comparative Example C-3, which has the chemical composition shown in Table 1 and is a bulk material having no concentration gradient of cobalt (single-layer structure), was subjected to measurement of saturation magnetic flux density Bs and iron loss Pi. The thickness was about 200 μm.
[0114] (Reference example R-1) A magnetic material according to Reference Example R-1 having a three-layer structure with no concentration gradient of cobalt and the chemical composition shown in Table 1 was prepared and subjected to measurement of saturation magnetic flux density Bs and iron loss Pi. This magnetic material was obtained by simply laminating a foil material of Fe-50Co alloy and a foil material of pure Fe, which is half the thickness of the foil material, in the same arrangement as in Example T-1, without carrying out heat treatment. The thickness was about 200 μm.
[0115] [Iron loss measurement] The iron loss was measured as follows: 4cm x 10cm test pieces were taken from each of the magnetic materials produced. The iron loss Pi (unit: W / kg) of the test pieces was measured under the conditions of a magnetic flux density of 1.0T, 400Hz, and a temperature of 20℃ using the H coil method with a BH loop analyzer (IFG, IF-BH550) and a vertical yoke single plate tester.
[0116] [Measurement of saturation magnetic flux density] The saturation magnetic flux density was measured as follows: 4cm x 10cm test pieces were taken from each of the magnetic materials produced. Using a vibrating sample magnetometer (VSM, Riken Denshi Co., Ltd., BHV-525H), the magnetization (unit: emu) of the test pieces was measured at an applied magnetic field of 1.6MA / m and a temperature of 20℃, and the saturation magnetic flux density Bs (unit: T) was calculated from the volume and mass of the test pieces.
[0117] [Structural observation and composition analysis] The observation of the alloy structure and the analysis of the chemical composition were carried out according to the following procedure. Test pieces measuring 4 cm x 10 cm were taken from each of the prepared magnetic materials. Using a scanning electron microscope (SEM, Hitachi High-Technologies Corporation, S-3400N) at 15 kV, backscattered electron images were observed in the cross-sectional direction of the test pieces, and the components were analyzed by SEM-EDX.
[0118] Table 1 shows the chemical composition of each magnetic material, the heat treatment conditions, and the measurement results of iron loss and saturation magnetic flux density.
[0119] [Table 1]
[0120] As shown in Table 1, Examples T-1 and T-2, which have a cobalt concentration gradient, exhibited a similar high saturation magnetic flux density Bs compared to Comparative Example C-3, which has the same overall chemical composition. Examples T-1 and T-2 exhibited reduced iron loss Pi compared to Comparative Example C-3. It was confirmed that forming a cobalt concentration gradient makes it possible to achieve both a high saturation magnetic flux density Bs and low iron loss Pi.
[0121] 7 and 8 are images showing a backscattered electron image by a scanning electron microscope and the results of composition analysis of the magnetic material according to the example. 7 and 8 show a backscattered electron (BSE) image of a cross section of a magnetic material taken with a scanning electron microscope (SEM) and a composite SEM-EDX spectrum analyzed in the cross section direction of the magnetic material. Fig. 7 shows the results of Example T-1. Fig. 8 shows the results of Example T-2.
[0122] As shown in Figures 7 and 8, when the laminate of the precursors was heat-treated to diffuse the cobalt atoms, a high-concentration region, a low-concentration region, and a concentration transition region were formed. It was confirmed that, compared to Example T-1, Example T-2 had a longer heat treatment time, so the thickness of the concentration transition region was enlarged and the thicknesses of the high-concentration region and the low-concentration region were reduced. [Explanation of symbols]
[0123] 1, 2, 3...magnetic material, 10...stator, 11...iron core, 12...stator slot, 13...slit, 14...teeth, 15...teeth claw portion, 20...stator coil, 21...segment conductor, 22...electrical insulating material, 100...high concentration region, 200...low concentration region, 300...concentration transition region
Claims
1. A magnetic material containing Fe and Co in a total amount of 90 mass% or more, The magnetic material is a foil or a plate, and contains 5% by mass or more and 40% by mass or less of Co and 0.1% by mass or more and 4.0% by mass or less of N; The steel contains at least one of an ordered phase α″-Fe 16 N 2 and a disordered phase α′-Fe 8 N in which N is dissolved, In the thickness direction of the foil or plate, A high concentration region having a cobalt concentration of 20 mass% or more; A low concentration region having a cobalt concentration of more than 0 mass% and not more than 10 mass%; a concentration transition region connecting the cobalt concentration of the high concentration region and the cobalt concentration of the low concentration region.
2. The magnetic material according to claim 1 , A magnetic material containing more than 0 mass% and 1.0 mass% or less of C.
3. The magnetic material according to claim 1 , Contains more than 0 mass% and not more than 1.0 mass% C, The ordered phase α″-Fe 16 N 2 and the disordered phase α'-Fe 8 A magnetic material in which N contained in at least one of the N atoms is replaced with C.
4. The magnetic material according to claim 1 , A magnetic material in which the concentration gradient of cobalt in the concentration transition region is 0.1 mass % / μm or more and 10 mass % / μm or less.
5. The magnetic material according to claim 1 , A magnetic material including a plurality of at least one of the high concentration regions and the low concentration regions.
6. 6. An iron core in which soft magnetic steel plates are laminated, the soft magnetic steel plates being partly or entirely formed of the magnetic material according to claim 1.
7. A method for producing a magnetic material containing Fe and Co, comprising the steps of: the magnetic material is a foil or a plate; A precursor formed of an iron-based material having a cobalt concentration of 20 mass% or more and a precursor formed of an iron-based material or a cobalt-based material having a cobalt concentration of more than 0 mass% and not more than 10 mass% are laminated together; heat-treating the precursors stacked on top of each other to diffuse atoms, thereby forming, in a thickness direction of the foil or plate, a high-concentration region having a cobalt concentration of 20 mass% or more, a low-concentration region having a cobalt concentration of more than 0 mass% and not more than 10 mass%, and a concentration transition region connecting the cobalt concentration of the high-concentration region and the cobalt concentration of the low-concentration region, thereby obtaining a magnetic material; The precursor or the magnetic material is subjected to a nitrous heat treatment in which a nitrous gas is brought into contact with the precursor or the magnetic material under heat treatment to cause nitrogen to penetrate and diffuse, and the precursor or the magnetic material that has been subjected to the nitrous heat treatment is rapidly cooled to cause a phase transformation into a martensite structure, A method for producing a magnetic material comprising: 5% by mass or more and 40% by mass or less of Co; and 0.1% by mass or more and 4.0% by mass or less of N; and comprising at least one of an ordered phase α″-Fe 16 N 2 and an irregular phase α′-Fe 8 N in which the N is dissolved.
Citation Information
Patent Citations
Magnetic material and manufacture thereof
JP1994267722A
Composite board laminate and method of manufacturing the same
JP2016092428A
Soft magnetic material, method for producing the same and electric motor using soft magnetic material
JP2020132894A
Soft magnetic material and method for producing the same, and electric motor containing soft magnetic material
US20220042157A1